2014
DOI: 10.1007/s00261-014-0196-8
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic adenocarcinoma: MRI conspicuity and pathologic correlations

Abstract: 3D FS T1 GRE arterial phase imaging produces greater pancreatic adenocarcinoma conspicuity compared to DWI but underestimates tumor size. DWI provides the best size evaluation but fails to delineate the tumor in one-fourth of cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 37 publications
0
32
0
1
Order By: Relevance
“…It must, however, be noted that in some instances the coexistence of chronic pancreatitis might lead to the relative preservation of the MR signal of the peritumoral pancreatic parenchyma on high-b-value DW images, thus leading to a decrease in the signal intensity ratio between the pancreas and the PanNEN [27]. As this could represent a possible source of false-negative results in DWI, patients with chronic pancreatitis must be examined with particular caution; probably, fsT2w images and the evaluation of secondary signs, such as deformation of the pancreatic contour or MPD/CBD dilation, might help in the precise localization of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…It must, however, be noted that in some instances the coexistence of chronic pancreatitis might lead to the relative preservation of the MR signal of the peritumoral pancreatic parenchyma on high-b-value DW images, thus leading to a decrease in the signal intensity ratio between the pancreas and the PanNEN [27]. As this could represent a possible source of false-negative results in DWI, patients with chronic pancreatitis must be examined with particular caution; probably, fsT2w images and the evaluation of secondary signs, such as deformation of the pancreatic contour or MPD/CBD dilation, might help in the precise localization of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection is the only curative treatment for this neoplasm, therefore the preoperative prediction of the pathological grade may have a smaller importance for PDAC management as compared to other pancreatic tumors. Some studies have tried to correlate DWI findings with the pathological grade, but results are controversial [43][44][45] . Details on the most relevant published studies are reported in Table 2.…”
Section: Pancreatic Tumorsmentioning
confidence: 99%
“…Details on the most relevant published studies are reported in Table 2. Overall, low-grade PDACs tend to present low ADC values [43][44][45] , but it still not clear which histological feature mainly contributes to diffusion restriction. Wang et al [43] and Muraoka et al [46] reported that tumors with limited glandular formation and dense fibrosis (i.e., paucicellular tumors) had lower ADC values as compared to welldifferentiated lesions characterized by neoplastic tubular structures; moreover, PDACs with dense fibrosis showed significantly lower ADC values than those with loose fibrosis.…”
Section: Pancreatic Tumorsmentioning
confidence: 99%
See 2 more Smart Citations